On Algebraic Manipulation Detection Codes from Linear Codes and their Application to Storage Systems - Harshan, Jagadeesh (2016)
Algebraic Manipulation Detection (AMD) codes form a cryptographic primitive designed to detect data corruption of the form of an additive operation in an Abelian group. In this paper, we discuss the applicability of AMD codes to protect erasure-code based storage systems from a Byzantine adversary injecting fake data in the distributed storage system. We study a special class of AMD codes which relies on classical linear codes for its construction. We explore the design aspects of such AMD codes namely, (i) understanding its design criteria, (ii) studying the fundamental limits of such codes, to facilitate data integrity, and (iii) present some examples.